This works becasue 1 n 1 n 1 2 1 2 21 n1 n1 n n

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = −1 to see that B = −1. This works becasue −1 n + 1 − (n − 1) 2 1 + = =2 . 2−1 n−1 n+1 n n −1 (a) We see that M sM = 1 2−1 − ···+ = = 1 1 + 1 2+1 1 3−1 + 1 (M −2)−1 1 1 − ···+ 1 2 M 2 1 1 = = − 2−1 n n−1 n+1 n=2 n=2 − 1 3 1 3+1 + 1 4−1 1 (M −2)+1 + 1 (M −1)−1 + 1 M −3 + ···+ − 1 2 1 1 + 3−1 4 5 1 1 M −1 + M −2 − − + + − 1 4+1 + − + 1 5−1 − 1 (M −1)+1 1 4 1 M − 1 6 + − + − + 1 M −1 1 M +1 − = (b) The sum of the series is 3 3 1 1 . − − = M →∞ 2 M M +1 2 lim sM = lim M →∞ 1 1 5+1 +... 1 M −1 − 1 M +1 +... +... 1 M − 1 M +1 1 1 3 − − . 2M M +1...
View Full Document

This document was uploaded on 03/23/2014 for the course MATH 142 at South Carolina.

Ask a homework question - tutors are online